KEKUASAAN DEWAN PERWAKILAN RAKYAT DALAM PENGGUNAAN HAK ANGKET MENURUT UNDANG-UNDANG DASAR 1945 - Purnamawati, Evi (Solusi, 2019)
This study analyzes the power of the questionnaire rights of the House of Representatives of the Republic of Indonesia. The House of Representatives is a House of Representatives and holds the power to form laws. The House of Representatives has the functions of legislative and legislative oversight. This research uses research methods using the method of literature (ribarary research). Type of normative juridical research through approaching legislation and conceptual approach of the research results of the House of Representatives, which essentially has the power to form the current law, the power began to widen towards supervision and budget, actually with the oversight function of the House of Representatives (DPR) towards the executive in practice the meaning of the teaching of separation of powers began to shift, the teaching of separation of powers between state institutions must not intervene with one another. In carrying out its functions the DPR has the right of Interpellation which is the right to request information from the Government in handling Government policies that have an impact on the life of society and the state. In addition, the DPR has the Right to Question, namely the Right to Investigate Government policies that are alleged to be in conflict with laws and regulations and express opinions outside the institution. Members of the DPR have the right to submit draft laws, ask questions, submit proposals and opinions, defend themselves, the right of immunity, and the right to protocol. The recommendation of this research is that the writer suggests that the DPR should make the regulation on questionnaire rights clearer especially about the process of using the questionnaire right so that there is no multi-interpretation so that violations do not occur in the process of using the inquiry right.